(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A geomagnetic storm is a global disturbance in Earth’s magnetic field usually occurred due to abnormal conditions in the interplanetary magnetic field (IMF) and solar wind plasma emissions caused by various solar phenomenon. A study of 220 geomagnetic storms associated with disturbance storm time (DST) decreases of more than -50 nT to -300 nT, observed during 1996-2007, the span of solar cycle 23 24. We have been analyzed and studied them statistically. We find yearly occurrences of geomagnetic storm are strongly correlated with 11-year sunspot cycle, but no significant correlation between the maximum and minimum phase of solar cycle-23 24 have been found. It is also found that solar cycle-23 24 are remarkable for occurrence of intense geomagnetic storm during its declining phase.